Sources of parental burden in a UK sample of first-generation North Indian Punjabi Sikhs and their white British counterparts. - Lloyd, H; Singh, P; Merritt, R; Shetty, A; Singh, S; Burns, T (2013)
OBJECTIVE: The correlates of parental burden in schizophrenia may differ between ethnic groups, but few studies have examined this in a UK setting. Our aim was to identify the correlates of burden in a UK sample of first-generation North Indian Punjabi Sikh parents and their white British counterparts. METHOD: Test the association of burden with a series of clinical, social and service use variables and control for potential confounding factors in a model predicting drivers of burden in a combined sample of the above. RESULTS: The strongest correlates of burden were patient symptoms and parental distress. Differences in correlates of burden between the groups emerged when individual components of service use and parental social network were tested. The group comparisons also revealed differences in expressed emotion (EE) and social networks. CONCLUSION: The similarities in sources of burden between the groups could be explained by a commonality of sociocultural and economic experience, resulting from the successful acculturation and affluence of this British Sikh group. The differences between the groups may be related to enduring cultural factors such as kin support, since larger family groups were associated with low burden in the British Sikh group. The nature of EE in this British Sikh group may explain why it was not associated with burden in this sample.